2020
DOI: 10.1111/jocd.13869
|View full text |Cite
|
Sign up to set email alerts
|

An unusual adverse event of botulinum toxin injection in the lower face

Abstract: The injection of botulinum toxin A (BoNTA) is one of the most used cosmetic procedures for the treatment of dynamic facial wrinkles.The low rate of side effects and the great satisfaction of the patient with the results contribute to the increasing popularity of this procedure. 1 Botulinum toxin A is traditionally used on the upper third of the face to reduce wrinkles and improve eyebrow positioning. Currently, there is a tendency to apply BoNTA all over the face and neck, in order to improve facial contour, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…10 Cadaver dissection studies have shown that the DAO overlaps the DLI inferiorly where the muscles arise from the mandibular border. 5,11,12 A potential side effect of DAO injection is therefore inadvertent injection of the DLI, 13 and injection of the DAO should therefore always remain lateral.…”
Section: Discussionmentioning
confidence: 99%
“…10 Cadaver dissection studies have shown that the DAO overlaps the DLI inferiorly where the muscles arise from the mandibular border. 5,11,12 A potential side effect of DAO injection is therefore inadvertent injection of the DLI, 13 and injection of the DAO should therefore always remain lateral.…”
Section: Discussionmentioning
confidence: 99%
“…Adverse smile events may occur during treatment of the hyperactive upper lip of gummy smile, the small vertical wrinkles above the upper lip that run vertically downward into the lip and are known as “barcode” lines, and when trying to induce a depressor anguli oris (DAO) muscle relaxation. 29…”
Section: Botulinum Toxin and The Facial Middle Thirdmentioning
confidence: 99%
“…Other side effects of facial muscles injection include eye dryness [ 8 ], eye weakness [ 9 ], ocular itching [ 10 ], diplopia [ 10 ], blurred vision [ 1 ] and hematoma in the injection site [ 11 ], which seem to be secondary to either upper or lower eyelid injections. Smile asymmetry or mouth droop occur due to injections of the muscles generating the smile function, i.e., the lower eyelid or lower parts of the face [ 12 ]. The decision to treat the lower eyelid with 1-point or 2-points injection is randomly taken and there is no consensus regarding this debate.…”
Section: Introductionmentioning
confidence: 99%